Child feeding and human rights - Kent George (BMC, 2006)
Abstract Background The human right to adequate food needs to be interpreted for the special case of young children because they are vulnerable, others make the choices for them, and their diets are not diverse. There are many public policy issues relating to child feeding. Discussion The core of the debate lies in differences in views on the merits of infant formula. In contexts in which there is strong evidence and a clear consensus that the use of formula would be seriously dangerous, it might be sensible to adopt rules limiting its use. However, until there is broad consensus on this point, the best universal rule would be to rely on informed choice by mothers, with their having a clearly recognized right to objective and consistent information on the risks of using different feeding methods in their particular local circumstances. Summary The obligation of the state to assure that mothers are well informed should be viewed as part of its broader obligation to establish social conditions that facilitate sound child feeding practices. This means that mothers should not be compelled to feed in particular ways by the state, but rather the state should assure that mothers are supported and enabled to make good feeding choices. Thus, children should be viewed as having the right to be breastfed, not in the sense that the mother is obligated to breastfeed the child, but in the sense that no one may interfere with the mother's right to breastfeed the child. Breastfeeding should be viewed as the right of the mother and child together.